Activated carbon monoliths derived from bacterial cellulose/polyacrylonitrile composite as new generation electrode materials in EDLC. (15th November 2018) - Dobashi, Ayumi; Maruyama, Jun; Shen, Yehua; Nandi, Mahasweta; Uyama, Hiroshi
Graphical abstract: Highlights: Activated carbon monolith with a co-continuous porous structure was fabricated. Polyacrylonitrile (PAN)/bacterial cellulose (BC) monolith was used as precursor. BC nanofibers entwined in porous PAN skeleton gives continuous carbon matrix. Grain boundary impedance is very small even without external conductive agent. Good electrode material for EDLC with high-speed charge/discharge capability. Abstract: Bacterial cellulose (BC) gel is synthesized by static culture process at the interface between air and medium. The solvent-exchanged BC gel is incorporated into polyacrylonitrile (PAN) copolymer solution under heating at 90 °C and subsequent cooling gives bacterial cellulose-polyacrylonitrile composite (BC-PAN ) monolith. TheBC-PAN monolith is carbonized at 1000 °C with physical activation in the presence of CO2 to obtain the activated carbon monolith, BC-PAN-AC, with large surface area and high microporosity. Unique morphologies are observed for BC gel which is propagated to theBC-PAN monolith and restored inBC-PAN-AC . The BC nanofibers remain entwined throughout the porous skeleton of the PAN backbone and the entangled structure helps in retaining the continuity of the matrix ofBC-PAN-AC and reduce the grain boundary impedance for electrical conduction. Cyclic voltammetry shows that these activated carbons are good electrode materials in electric double layer capacitors (EDLC) with capability of high-speed charging and discharging.